Problem-based learning in the college music classroom - Sarrazin, Natalie Rose (Routledge, 2019)
Problem-Based Learning in the College Music Classroom explores the core tenets of Problem-Based Learning (PBL). PBL is an effective, student-centered approach in which students learn higher-order thinking skills and integrative strategies by solving real-world challenges--not often employed in music classrooms. Yet such courses are uniquely situated to advance this innovative pedagogical approach. This volume sheds light on PBL best practices in survey-and topic-based music courses while integrating general education content, discussing implementation, materials, methods, and challenged, and encouraging readers to think creatively to develop flexible solutions for large-scale issues--back cover